2002
DOI: 10.1088/0268-1242/18/2/303
|View full text |Cite
|
Sign up to set email alerts
|

A model for capacitance reconstruction from measured lossy MOS capacitance voltage characteristics

Abstract: A capacitance model is developed and a correction formula is derived to reconstruct the intrinsic oxide capacitance value from measured capacitance and conductance of lossy MOS devices. Due to discrepancies during processing, such as cleaning, an unwanted lossy dielectric layer is present in the oxide/semiconductor interface causing the measured capacitance in strong accumulation to be frequency dependent. The capacitance-voltage characteristics after correction are free from any frequency dispersion effect an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(42 citation statements)
references
References 24 publications
0
40
0
Order By: Relevance
“…Figure 6 depicts the C-V characteristics of the Al/BTO/p-Si devices for two different frequencies, namely, 1 KHz and 100 KHz. Extra care needs to be taken for the capacitive response according to the method proposed by Kwa et al 23 The overall behavior is indeed that of a MOSCAP, with the three distinct regimes of accumulation-depletion-inversion clearly shown.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 6 depicts the C-V characteristics of the Al/BTO/p-Si devices for two different frequencies, namely, 1 KHz and 100 KHz. Extra care needs to be taken for the capacitive response according to the method proposed by Kwa et al 23 The overall behavior is indeed that of a MOSCAP, with the three distinct regimes of accumulation-depletion-inversion clearly shown.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that increasing frequency causes an increase in relaxation times and the energy of charge carrier [31]. The dispersion of relaxation times depends on the grain boundaries and various grains in all three structures [27][28][29][30][31]. The behavior of one peak in M may result from the existence of a particular density distribution profile of interface states at all three interfaces.…”
Section: Resultsmentioning
confidence: 97%
“…However, dipolar polarization may occur in high or intermediate frequency range of 1 kHz to 1 MHz because of the longer relaxation time and may result from the location of surface charges, impurities, orientable dipoles [24][25][26]. The interfacial polarization at f < 10 13 Hz is principally more sensitive [27]. In particular, when a physical barrier that inhibits charge migration impedes mobile charge carriers, the interfacial polarization occurs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As seen in Fig. 4(a), in the presence of a series resistance, the capacitance in the C-V plots has an anomalous peak for each temperature as in many studies [22][23][24][25]. To obtain the real diode capacitance C c and conductance G c /w, the high frequency capacitance measured under forward and reverse biases was corrected for the effect of series resistance using Eqs.…”
Section: Resultsmentioning
confidence: 99%